2021
DOI: 10.1021/acs.jmedchem.1c00019
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Optimization of 2H-1λ2-Pyridin-2-one Inhibitors of Mutant Isocitrate Dehydrogenase 1 for the Treatment of Cancer

Abstract: Neomorphic mutations in isocitrate dehydrogenase 1 (IDH1) are oncogenic for a number of malignancies, primarily low-grade gliomas and acute myeloid leukemia. We report a medicinal chemistry campaign around a 7,7-dimethyl-7,8-dihydro-2H-1λ2-quinoline-2,5­(6H)-dione screening hit against the R132H and R132C mutant forms of isocitrate dehydrogenase (IDH1). Systematic SAR efforts produced a series of potent pyrid-2-one mIDH1 inhibitors, including the atropisomer (+)-119 (NCATS-SM5637, NSC 791985). In an engineered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Inhibiting mutant IDH1 has been clinically validated, with ivosidenib (AG-120) approved by the FDA for the treatment of relapsed/refractory AML . A handful of other small molecule mutant IDH1 inhibitors, including IDH1/2 dual-inhibitor AG-881, BAY-1436032, GSK321, IDH305, FT-2102, and others, , have also shown efficacy in various preclinical and clinical studies, potentially offering new treatment options for different tumor types carrying IDH1 mutations.…”
mentioning
confidence: 99%
“…Inhibiting mutant IDH1 has been clinically validated, with ivosidenib (AG-120) approved by the FDA for the treatment of relapsed/refractory AML . A handful of other small molecule mutant IDH1 inhibitors, including IDH1/2 dual-inhibitor AG-881, BAY-1436032, GSK321, IDH305, FT-2102, and others, , have also shown efficacy in various preclinical and clinical studies, potentially offering new treatment options for different tumor types carrying IDH1 mutations.…”
mentioning
confidence: 99%
“…Replacement of the terminal piperazine element of the mutant isocitrate dehydrogenase 1 (IDH1) inhibitor 213 with 2,6-diazaspiro[3.3]­heptane in compound 214 was an effective molecular edit that preserved enzyme inhibitory potency, although in this example, there was no significant improvement in developability properties …”
Section: Azetidine-based Bioisosteres Of Piperazinementioning
confidence: 99%
“…Over 14 days of drug administration at doses of 200−600 mg/day, the mean reduction in RBC 2,3-DPG levels was claimed to be 56% along, with a 68% increase in ATP concentrations. Interestingly, FT709 (115), an analogue of compound 114, has recently been characterized as a potent and selective inhibitor of the catalytic acitvity of the deubiquitylase (DUB) enzyme USP9X, with an IC 50 value of 82 nM, in a biochemical assay. 51 The hexahydropyrrolo [3,4-c]pyrrole heterocycle 9 has also found application as a replacement for piperazine and other heterocycle-based scaffolds in the design of inhibitors of autotaxin (ATX), a lysophospholipase D enzyme that converts lysophosphatidylcholine into lysophosphatidic acid (LPA).…”
Section: Octahydropyrrolo[34-c]pyrrole Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Jason M. et al reported a class of mIDH1 inhibitors with 2H-1λ2-Pyridin-2-one backbone ( Rohde et al, 2021 ). The most potent compound 14 ( Figure 8B ) inhibits IDH1 R132H/R132C with IC 50 values of 81 and 72 nM, respectively.…”
Section: Isocitrate Dehydrogenase Mutant Inhibitorsmentioning
confidence: 99%